Effect mechanism of H3PO4 on the formation and transformation of persistent free radicals in biochar - Yajie Gao; Yuan Gao; Aimin Li (Biochar)
Abstract Persistent free radicals (PFRs) in biochar have attracted wide attention due to their multifaceted roles in the environment. The regulation of PFRs in biochar is not only beneficial to broaden its application potential, but also eliminates its environmental risks. However, as a common biochar modification reagent, phosphoric acid (H3PO4) has not been studied in the field of PFRs regulation. Herein, this study systematically investigated the effect of H3PO4 on PFRs in biochar under various conditions. The results indicated that H3PO4 promoted the formation of PFRs in biochar at low pyrolysis temperature (< 500 °C), owing to the positive effect of catalytic cross-linking on the degradation of biomass precursor. Yet, H3PO4 reduced PFRs in biochar at high pyrolysis temperature (≥ 500 °C), since the capture of H∙ or HO∙ by PO∙ and the steric hindrance changed by H3PO4, which caused the rearrangement and polycondensation of carbon structure. H3PO4 also favored carbon-centered PFRs as the dominant type. The ingredients of biomass precursor, including cellulose, Fe, Ti, protein, etc., contributed to different effects on PFRs under H3PO4 modification. This study provided new insights into the roles of H3PO4 on the formation and transformation of PFRs in biochar, coupled with regulation strategies in the practical application. Graphical Abstract